Diversifikation und Wachstum landwirtschaftlicher Unternehmen; Diversification and Growth of Farms - Christoph Weiss; Holger Thiele (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– The liberalization of agricultural markets has increased the interest of farmers (as well as those working on policies concerned with their welfare) in agricultural diversification strategies. However, empirical research on diversification in European agricultural markets is very limited. This paper follows OUSTAPASSIDIS (1992) and investigates the relationship between different diversification strategies and farm performance (farm growth rates). The results of fixed- and random-effect models for approx. 3900 farms in Schleswig-Holstein for the period 1988/89-1997/98 show that diversification into related products increases growth rates whereas the opposite applies for diversification into unrelated products. Initial farm size has a significant and negative impact on the rate of growth which implies ß-convergence of farm sizes.
Keywords: 330; Landwirtschaft; Diversifikation; Betriebsgröße; Unternehmenswachstum; Schätzung; Schleswig-Holstein; Deutschland